Chrześcijaństwo a edukacja w dobie ponowoczesności = Christianity and education in the area of post-modernity - Nowak-Łojewska, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski)
The article deals with the possibilities of using assumptions of Christianity in education. It consists of two parts. The first part presents the post-modern context of contemporary education. The second one shows the aspects of Christianity in education. The article ends with the personal reflection of the author, who emphasises of the biblical view of the Christian vision of education.
Keywords: edukacja; postmodernism; chrześcijaństwo